Anesthesia Methods in Pregnant Women: A Review Study - Zahid Hussain Khan (Tehran University of Medical Sciences, 2021)
Background: Manage and deal with the pregnant patient undergoing anesthesia for surgical non-obstructed surgery, assess the effects of non-obstetric surgeries on both fetus and mother during pregnancy, and measures to prevent it. Methods: A review search study was currently managed in PubMed, MEDLINE, Embase, Science gate, Elsevier, Scientific report, Google Scholar, and Cochrane Evidence-Based Medicine Reviews, after obtaining approval from the ethics committee of Tehran University of Medical Sciences. All the reviews identified were restricted to human studies and available in English. Results: Elective surgery ideally should be avoided during pregnancy while emergency surgery should proceed with consideration for the anesthetic implications of the altered physiology of pregnancy. Caution must be taken during anesthetic application and Airway management. Conclusion: Pre-oxygenation is essential and consider the rapid-sequence induction accompanied with cricoid pressure to lower the incidence of aspiration.  lower MAC values of the volatile anesthetic should be used and medications titrated to preferably produce beneficial effects only.